Systematic Isolation of Key Parameters for Estimating Skeletal Maturity on AP Hip Radiographs. Issue 8 (September 2021) - Furdock, Ryan J.; Benedick, Alexander J.; Nelson, Grant; Li, Don; Cooperman, Daniel R.; Sanders, James O.; Liu, Raymond W.
Abstract : Background: The ability to estimate skeletal maturity using a hip radiograph does not yet exist, but may have utility in the treatment of scoliosis, slipped capital femoral epiphysis, and lower limb deformity. We sought to develop a fast, accurate, and reproducible method. Methods: Fourteen hip radiologic parameters were evaluated on serial anteroposterior hip radiographs from 3 years before to 2 years after the skeletal age associated with 90% of final height, a validated skeletal maturity definition which correlates with the timing of peak height velocity. The Greulich and Pyle (GP) left hand bone age was obtained for comparison. Stepwise linear regression and generalized estimating equation analyses were used to isolate key hip and demographic parameters, creating the "optimized Oxford" skeletal maturity system. The accuracy of the optimized Oxford system in predicting years from 90% of final height was evaluated and compared with systems of demographics only, the modified Oxford, demographics+modified Oxford, and demographics+GP. Results: A total of 284 hip radiographs from 41 girls (range: 7 to 15 y) and 38 boys (range: 9 to 17 y) were included. Following multivariate analyses, 5 of the original 14 hip radiographic parameters remained significant. The predictions made by the optimized Oxford model had greater accuracy and fewer outlier predictions (predictions >1 y off from actual years from 90% of final height) than the demographics only and modified Oxford only models ( P <0.05 for all). The optimized Oxford model had greater prediction accuracy than the demographics+modified Oxford model, but similar rates of outlier predictions ( P =0.903). No differences in mean prediction accuracy or rate of outlier predictions were observed between the optimized Oxford and the demographics+GP model ( P >0.05). Conclusion: High precision in skeletal maturity estimation can be achieved by using chronological age, sex, and 5 hip radiographic parameters. Clinical Relevance: We have developed a skeletal maturity system that utilizes anteroposterior hip radiographs and performs as accurately as GP.